18F-FDG PET/CT in a Seldom Case of Primary Duodenal Dermatofibrosarcoma Protuberans With Lung and Skeletal Metastases. (February 2015) - Karunanithi, Sellam; Jain, Tarun Kumar; Singh, Ashok; Bal, Chandrasekhar; Kumar, Rakesh
<x xml:space="preserve">Abstract</x> Abstract Dermatofibrosarcoma protuberans (DFSP) is an uncommon cutaneous soft tissue sarcoma tumor that arises from the dermis of the skin. Sarcomas of the intestines are rare, and a DFSP arising from the small intestine is a very rare occurrence. Here we present 18F-FDG PET/CT imaging findings of a 60-year-old man with DFSP in the duodenum with metastases to the lung, mesentery, and skeleton.